ORTHOSTATIC REACTIONS OF DIASTOLIC BLOOD PRESSURE IN PATIENTS WITH PERMANENT FORM OF ATRIAL FIBRILLATION - Chorna, Yu. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
A relationship between different types of orthostatic reactions (OR) of diastolic blood pressure (DBP) and clinical manifestation of permanent form of atrial fibrillation (AF) in 73 patients aged 68,9 ± 9,3 years has been studied. All types of OR of SBP have been noticed in studied population.  Hypotensive (40 %) and isotensive (38 %) OR of DBP have been dominanted, hypertensive OR of DBP have been met rarely (22 %). 3 % of patients had qualified hypotensive OR of DBP, suchlike hypertensive OR haven’t been met in our study. Hypotensive OR of DBP have been more frequently met in elderly people with severe arterial hypertension  and ejection fraction less then 40 %, isotensive – in old-aged patients with mild arterial hypertension.